1997
DOI: 10.1046/j.1365-2443.1997.1560354.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the cDNA for the catalytic subunit of plant DNA polymerase α and its cell‐cycle dependent expression

Abstract: Background: DNA polymerase a has been studied in considerable detail in yeast and animals. Genetic and biochemical analyses reveal that this enzyme is composed of a heterotetramer and is necessary for replicon initiation and primer synthesis in lagging strand synthesis. In spite of the fact that modes of DNA replication in plants seem to be similar to those in other eukaryotes, very little is known about the biochemical components that participate in DNA replication of plants, including DNA polymerases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…3A and coexpressed with p54-p46 in COS-1 cells. An alignment of amino acid sequences of DNA polymerase ␣ from Saccharomyces cerevisiae, Schizosaccharomyces pombe, Drosophila melanogaster, Trypanosoma brucei, humans, mice, and Oryza sativa allowed us to choose domain boundaries for construction of mutants with deletions (22,44). The subcellular distribution of the deletion mutants was determined by immunodetection with an anti-six-His monoclonal antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A and coexpressed with p54-p46 in COS-1 cells. An alignment of amino acid sequences of DNA polymerase ␣ from Saccharomyces cerevisiae, Schizosaccharomyces pombe, Drosophila melanogaster, Trypanosoma brucei, humans, mice, and Oryza sativa allowed us to choose domain boundaries for construction of mutants with deletions (22,44). The subcellular distribution of the deletion mutants was determined by immunodetection with an anti-six-His monoclonal antibody.…”
Section: Resultsmentioning
confidence: 99%
“…However, even though the precise roles of DNA polymerases ␣ and ␦ have been established for the SV40 DNA replication system, the way in which these enzymes function during replication of the chromosome is still not clear. Namely, we are ignorant about the architecture of the subunit assemblies in the replication complexes, the way in which the activities of these complexes are regulated, the coordination that must exist between these polymerases at the replication fork, and which DNA polymerase, ␦ or ε, participates in the elongation of the leading strand and lagging strand (3,4,34).DNA polymerases ␣, ␦, ε, and contain amino acid sequences that are conserved among a wide range of DNA polymerases, indicating that these polymerases belong to the class B DNA polymerase family (32,42,44). During this decade, molecular cloning analysis has shown that the large subunits of all these DNA polymerases comprise the catalytic activity, whereas the functions of the smaller subunits, with the exception of the primase subunit, still remain uncertain (12,34,42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Protein complexes containing polymerase and primase activity have been purified from a variety of plant systems (Coello and Vazquez-Ramos, 1995;Garcia et al, 2002), demonstrating that a POLA-like function exists in plants. However, sequence homology has been investigated only for the POLA1 subunit in rice (Yokoi et al, 1997). Rice POLA1 was originally reported to be shorter than other eukaryotic POLA1 homologs, due to a truncated N terminus (Yokoi et al, 1997).…”
Section: Elongation Complexmentioning
confidence: 99%
“…However, only fragmentary information is available. Apart from basic descriptions of rice (Oryza sativa) genes coding for the homologs of the catalytic subunit of Pola, of two subunits of Pold, and of the replication accessory proteins FEN1 and PCNA (Yokoi et al, 1997;Kimura et al, 2001;Uchiyama et al, 2002), most functional studies of core replication genes, including mutational analysis, were performed in Arabidopsis thaliana. Of the three replicative DNA polymerases, the catalytic subunit of Pola (INCURVATA2) (Barrero et al, 2007) and two of the four subunits of Pol« (Jenik et al, 2005;Ronceret et al, 2005;Yin et al, 2009) were characterized.…”
Section: Introductionmentioning
confidence: 99%